Implementasi Metode Naive Bayes - Weighted Product Untuk Diagnosa Penyakit Ikan Kerapu - Annam Rosyadi; Edy Santoso; Mochammad Ali Fauzi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Grouper (Epinephelus sp.) Is a fish that lives in seawater that has high economic value, so it is consumed by many Indonesians because of its delicious taste. However, during grouper cultivation, there are problems that arise, namely the existence of diseases that can cause death. Usually in the grouper, there are many diseases that originate from bacteria, parasites, viruses, and other sources, namely lack of nutrition and decreasing water quality in ponds. So that the existence of this system can provide information to pond farmers about the types of diseases in groupers and handling that can be given. In this system using the naive bayes - weighted product method. The Naive Bayes method serves to search for probability values for each symptom in the disease. The weighted product method serves to draw conclusions on the diagnosis of grouper disease using alternative values of S and V criteria. There are 6 diseases and 16 symptoms in groupers in this system. Accuracy testing using a lot of data as much as 100 test data obtained an accuracy value of 94%.